Delayed Time-to-Treatment of an Antisense Morpholino Oligomer Is Effective against Lethal Marburg Virus Infection in Cynomolgus Macaques. - Travis K Warren; Chris A Whitehouse; Jay Wells; Lisa Welch; Jay S Charleston; Alison Heald; Donald K Nichols; Marc E Mattix; Gustavo Palacios; Jeffrey R Kugleman; Patrick L Iversen; Sina Bavari (Public Library of Science (PLoS), 2016)
Marburg virus (MARV) is an Ebola-like virus in the family Filovirdae that causes sporadic outbreaks of severe hemorrhagic fever with a case fatality rate as high as 90%. AVI-7288, a positively charged antisense phosphorodiamidate morpholino oligomer (PMOplus) targeting the viral nucleoprotein gene, was evaluated as a potential therapeutic intervention for MARV infection following delayed treatment of 1, 24, 48, and 96 h post-infection (PI) in a nonhuman primate lethal challenge model. A total of 30 cynomolgus macaques were divided into 5 groups of 6 and infected with 1,830 plaque forming units of MARV subcutaneously. AVI-7288 was administered by bolus infusion daily for 14 days at 15 mg/kg body weight. Survival was the primary endpoint of the study. While none (0 of 6) of the saline group survived, 83-100% of infected monkeys survived when treatment was initiated 1, 24, 48, or 96 h post-infection (PI). The antisense treatment also reduced serum viremia and inflammatory cytokines in all treatment groups compared to vehicle controls. The antibody immune response to virus was preserved and tissue viral antigen was cleared in AVI-7288 treated animals. These data show that AVI-7288 protects NHPs against an otherwise lethal MARV infection when treatment is initiated up to 96 h PI.